Graphical Models, Potential Outcomes and Causal Inference: Comment on Ramsey, Spirtes and Glymour - Lindquist, Martin A. (2010)
Ramsey, Spirtes and Glymour (RSG) critique a method proposed by Neumann et al (2010) for the discovery of functional networks from fMRI meta-analysis data. We concur with this critique, but are unconvinced that directed graphical models (DGMs) are generally useful for estimating causal effects. We express our reservations using the “potential outcomes” framework for causal inference widely used in statistics.